Pragmatic Meanings of Karonese Proverbs Spoken in Wedding Party - Barus, E (KnE Social Sciences, 2018)
Pragmatics is the subfield of linguistics which studies language and focuses on the users and the context of language rather than reference truth, or grammar. The aim of this article is to analyze the pragmatic meanings of Karonese proverbs spoken in the wedding party. It has become the Karo custom to advise the bride and the bridegroom in a wedding party by using wise words and proverbs. Such a ceremony is known as advisory expressions and explanatory meanings. The meanings are based on pragmatics which can be classified into three types: explanatory meaning, psychological meaning, and social meaning. The method of research applied in this study is qualitative research in which the data were based on some references in the library. This is also a field research as some of the data were obtained from respondents who expressed advisory speech to the bride and the bridegroom in wedding parties. This study applies Cass’ (2012) theory of pragmatic usage which focuses on the inferred meaning that the speakers and listeners perceive, referring to Karonese proverbs spoken by family members and the married couple as the listeners. The results of this research are: (1) Karonese proverbs are commonly expressed in advisory speech of a wedding party that is addressed to the couple, (2) Among the three types of meaning discussed here, the social meanings are found most dominant. It can be concluded that the analysis of pragmatic meanings of the Karonese proverbs is very significant for language learners and for a newly married couple as to comprehend good advice from the elderly so that they can apply the advice in their new life. This is also significant as an attempt to preserve the asset of Indonesian culture, Karonese custom in Indonesia. Keywords: Pragmatic meaning, explanatory meaning, psychological meaning, social meaning, Karonese proverb.